THE EFFECT OF INTELLIGENCE AND ACADEMIC SUCESS ON SELF-PERCEPTIONS OF PRIMARY SCHOOL STUDENTS - Yüksel, Müge; Özgen, Gülşen; Başer Baykal, Nur (International Online Journal of Education and Teaching, 2019)
The main aim of this study is to examine the relationship between intelligence levels, self-perception and academic achievement of fourth grade primary school students. The study was carried out with 36 students in a state school in Istanbul. In the study; demographic form containing the achievement scores of Turkish and Mathematics courses and personal information of the students, Wechsler Intelligence Scale for Children-Revised-WISC-R and Piers-Harris Children’s Self Concept Scale were applied. As a result of the findings, it can be said that the gender variable in the 4th grade students of elementary school is not related to the self-perception and academic achievement. In addition, it was found that intelligence score was related to mathematics scores at a high level, related to Turkish scores at a low level. However, there was no significant relationship between intelligence scores and self-concept. It was also shown that the achievement of Turkish and mathematics lessons predicted the information subtest that represents long-term memory in the verbal section of WISC-R and the achievement of the mathematics course predicted digit symbol subtest (psychomotor coordination and speed) in the performance section of WISC-R. In the study, there was not found any effect of intelligence and academic success on children's self-concepts.